Ulica Długie Pobrzeże - Nowaliński, Karol (1935- ). (Gdańsk, 1987)
Przedstawia Długie Pobrzeże w Gdańsku, 1987 r.
Tyt. i data napisane przez autora ołówkiem na rewersie.
Keywords: Fotografie -- Polska -- Gdańsk; Ulice -- Polska -- Gdańsk -- 1945- -- fotografie; Gdańsk (Polska) -- 1970-2000 -- fotografie